2019
DOI: 10.1182/blood-2019-128178
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Study of the Anti-TIM-3 Antibody MBG453 in Combination with Decitabine in Patients with High-Risk Myelodysplastic Syndrome (MDS) and Acute Myeloid Leukemia (AML)

Abstract: Co-senior authors Andrew Brunner and Andrew H. Wei contributed equally to this work Background: MBG453 is a high-affinity humanized anti-TIM-3 (T-cell immunoglobulin domain and mucin domain-3) IgG4 antibody in development for the treatment of MDS, AML, and other malignancies. TIM-3 is an immune checkpoint with a complex regulatory role in both adaptive and innate immune responses and is also preferentially expressed on leukemic stem and progenitor cells, making it a potential target in MDS and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…Ongoing clinical trials are largely investigating anti-Tim-3 in combination with anti-PD-1 in solid tumors. However, striking early trial data show efficacy of TIM-3 in combination with chemotherapy in myelodysplastic syndrome (MDS) and acute myelogenous leukemia (AML) 14 indicating its potential value in the treatment of hematologic malignancy and disorders.…”
mentioning
confidence: 99%
“…Ongoing clinical trials are largely investigating anti-Tim-3 in combination with anti-PD-1 in solid tumors. However, striking early trial data show efficacy of TIM-3 in combination with chemotherapy in myelodysplastic syndrome (MDS) and acute myelogenous leukemia (AML) 14 indicating its potential value in the treatment of hematologic malignancy and disorders.…”
mentioning
confidence: 99%
“…T-cell immunoglobulin mucin (TIM-3) is another emerging target in immunotherapy, present on the surface of effector T-cells, whose hyperexpression and hyperactivation has been shown able to induce T-cell exhaustion in several cancers including myeloid malignancies [129][130][131].MBG453 is a TIM-3 antibody that is currently in study in several disease settings. Association with DEC in a phase I study of HMA-naïve, high-risk MDS patients showed CR of 50% (preliminary results NCT03066648) [132]. Ongoing studies are evaluating other combinatory schema with AZA (NCT03946670, NCT03940352) in higher risk MDS.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Consistent with a role in the negative regulation of anti-tumour immunity, there is extensive pre-clinical data demonstrating the therapeutic benefit of blocking TIM-3 signalling, mostly in conjunction with PD-1 blockade [ 242 ]. These encouraging pre-clinical results have led to development of TIM-3 blocking antibodies for clinical use, with several studies reporting early clinical findings and strong safety profiles when used in combination with αPD-1/PD-L1 or decitabine [ 243 , 244 , 245 ].…”
Section: Inhibitory Receptorsmentioning
confidence: 99%